Oral administration assessment of outer membrane proteins of Vibrio alginolyticus on the growth of giant freshwater prawns (Macrobrachium rosenbergii De Man) - Abiodun, Ajadi Abdullateef (2016)
The production of prawns is unarguably a fast-growing global aquaculture. This is evident in the culture of freshwater prawns which is rapidly gaining momentum in terms of productions and values in Malaysia and the world at large. Vibrio alginolyticus is one of the most pathogenic species of Vibrio that cause high mortality in freshwater prawns. The conventional use of antibiotics in the treatment of this disease has remained ineffective and resulted in an exponential increase in virulence and pathogenicity of the microbes. Hence, the need for better and practicable measures of disease prevention and treatment. This was the first study to investigate the effects of oral administration of outer membrane protein of vibrio in Macrobrachium rosenbergii experimentally infected with V. alginolyticus. Prawns were divided into three groups A, B, and C of 10 prawns each with replicates in 6 (150 L) glass aquaria. Group A was fed with OMPs-mixed diet, group B with OMPs-FIA (Freund's incomplete adjuvants) mixed diet while group C was fed with OMPs or adjuvant-free diet (control diet). Groups A and B were fed for seven days, alternated with control diet for seven days and a booster dose for another seven days. All prawns were weighed weekly, and haemolymph was collected to examine the total haemocytes counts (THC), phenoloxidase activity (PO) and the presence of OMPs in the haemolymph. All prawns were challenged intramuscularly with 50 μL of 107 CFU of V. alginolyticus. The results of the analysis revealed significance difference in mean weight gain and THC (P < 0.05) between the treated groups and the control but not with PO activity. Although there was no significant difference (P > 0.05) in the level of mortality in all the groups after 24 h, this was not unconnected to pains from the injection coupled with stress, as this was also observed in blank control (not challenged with V. alginolyticus). In the second experiment, 45 prawns were divided into three different groups of 15 prawns each. Group A was treated with formalin killed Vibrio cell by immersion only, B with OMPs by intramuscular injection and boosted by immersion and C with PBS by immersion only at days 0, 3, 5 and 7. A bacterial challenge was carried out by immersion on day 9 and observed for mortality for seven days. The total haemocyte count (THC) increased in the treatment groups more than the control but no significant difference in the level of THC increment between the treatment groups. There was no mortality in the treatment groups, but the mortality rate in the control group was 55% over the period of seven days. Haemolymph (both coagulated and non-coagulated) that was also collected to detect the presence of OMPs in the system using SDS-PAGE revealed no bands of OMPs but only those of the plasma proteins, this could be as a result of natural clearance activity of the prawns to get rid of foreign agents. Gross examination of the experimentally challenged prawns was carried out following the mortality and tissues were processed for histopathological lesions and immuno-histochemical reaction. The untreated group showed more pronounced lesions than the treatment groups. This study, however, concluded that oral administration of OMPs with or without Freund's incomplete adjuvant is a good growth promoter and has the potential for protection against vibriosis in Macrobrachium rosenbergii when administered with unique antigen protection vehicle and at appropriate dosages, but the protection may be for a short period of time.